2022
DOI: 10.3389/fnut.2022.1042425
|View full text |Cite
|
Sign up to set email alerts
|

Multiple health risk behaviors, including high consumption of ultra-processed foods and their implications for mental health during the COVID-19 pandemic

Abstract: Background and aimThe growing increase in diet- and behavior-related illnesses has drawn the attention of many epidemiologists who attribute such changes to the epidemiological and nutritional transition. Thus, this study aims to evaluate the association between the combined occurrence of health risk behaviors, such as sedentary lifestyles, high weekly consumption of ultra-processed foods (UPFs), and non-daily consumption of fruits and vegetables, and symptoms of anxiety or depression in adults.MethodsThis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…They found that individuals with high ultra-processed foods consumption were significantly more likely to report depression and anxiety and to have worse mental health. Other studies have found a similar association 35 , 36 , 37 . The physiological mechanisms associated with these events are not yet known; however, it has been hypothesized that industrial additives used for preservation, odorization, and coloring can modify the neuronal mitochondrial function by various metabolic pathways 38 .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…They found that individuals with high ultra-processed foods consumption were significantly more likely to report depression and anxiety and to have worse mental health. Other studies have found a similar association 35 , 36 , 37 . The physiological mechanisms associated with these events are not yet known; however, it has been hypothesized that industrial additives used for preservation, odorization, and coloring can modify the neuronal mitochondrial function by various metabolic pathways 38 .…”
Section: Discussionsupporting
confidence: 70%
“…This leads us to believe that the neural mechanisms associated with the consumption of ultra-processed foods 34 , 35 and increased WHtR 47 may lead to adolescents having a greater chance of developing CMD, even during adolescence. For us, based on our results and on those of published studies, the advertising and sale of ultra-processed foods in private schools, favoring greater consumption of these foods 48 , 49 and increased body adiposity, increase the risk of CMD in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Consumers of all types of food confirmed that octagons (which are labels on consumption warnings) are deficient , so other methods are needed to warn of the consequences of consumption [35], but in many countries, these labels are very important because they help to make a decision for the consumer as well as help to have nutritional policies, and these are very effective [37] because they prevent many cardiovascular diseases [38]. The consumption of these ultra -processed foods has effects on mental health, with symptoms of anxiety and depression in adults [42], and in underdeveloped countries, it was detected that schoolchildren consume these foods without any control [45], thus failing to consume quality foods rich in nutrients [46].…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of ultra -processed foods varies according to the socioeconomic level and geographic space, but everywhere it is associated with low-quality diets [41]. It is estimated that there is a relationship between the sociodemographic level and the selection of available foods [42]. A great concern arises in society tha nks to the increase in cases of diseases produced by low diet quality, and experts attribute it to important changes in terms of nutrition in the last decades [43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…All studies controlled for SES indicators, but not access to healthy nutritious food or food insecurity specifically. Food insecurity is associated with higher UPF consumption (24) and a recent epidemiological survey study estimates participants with the highest UPF consumption have a 60% higher prevalence of food insecurity (RR = 1.60) (25). Food insecurity is associated with elevated obesity risk in meta-analysis (OR = 1.53 ~ RR 1.42) (26) and effects appear similar when examined prospectively (27).…”
Section: Potential Residual Confoundingmentioning
confidence: 97%